Formation of Gradient Multiphase Nanostructured Surface Layers Using the Electron-Ion-Plasma Combined Method; Applied Mechanics and Materials; Vol. 756 : Mechanical Engineering, Automation and Control Systems (MEACS2014) - Ivanov Yu. F. Yuriy Fedorovich; Teresov A. D.; Ivanova O. V.; Gromov V. E.; Budovskikh E. A.; Klopotov A. A. (Material Engineering and Technologies, 2015)
Title screen